Waste to wealth: A sustainable circular bioeconomy approach of chicken manure powder for increasing productivity of Lanchester’s freshwater prawn (Macrobrachium lanchesteri) - Buncha Tongmee; Nattakarn Mukdajaturaphak; Yuwalee Unpaprom; Rameshprabu Ramaraj; Tipsukhon Pimpimol; Niwooti Whangchai (Maejo International Journal of Energy and Environmental Communication, 2021)
A biorefinery is ideal because it can combine many processes to produce multiple bio-products from organic solid waste. Moreover, in view of socially rising energy demands and biodiversity conservation, biorefinery contributed as a sustainable strategic tool for the emerging circular bio-economy. In this research objective was to study some techniques to increase the productivity of Lanchester’s freshwater prawn in earthen ponds. The experiment using a completely randomized design was conducted. In six Nattearthen ponds, different amounts of chicken manure were applied to produce different amounts of phytoplankton (green algae). The first pond was control, then, the 2nd to 6th ponds were applied with chicken manure in 30, 60, 90, 120 and 150 kg/rai/week, respectively. The prawns were fed twice daily with 5% of total body weight using 40% protein diet. The results of the study showed that feeding with different densities of phytoplankton (green algae) affected the productivity of Lanchester’s freshwater prawn significantly. The highest productivity of Lanchester’s freshwater prawn was 566.30 ±4.88 g from the pond applied with chicken manure of 120 kg/rai/week. The productivity of Lanchester’s freshwater prawn applied with 90, 30, 60, 150 and 0 kilograms/rai/week of chicken manure was 416.53 ± 9.89, 295.43 ± 5.46, 281.13 ± 4.63, 275.39±4.78 and 265.86 ±4.79 g, respectively. In conclusion, the effect of different densities of phytoplankton (green algae) increased the productivity of Lanchester’s freshwater prawn (Macrobrachium lanchesteri).